2012
DOI: 10.1074/jbc.m112.357327
|View full text |Cite
|
Sign up to set email alerts
|

Functional Asymmetries of Proteasome Translocase Pore

Abstract: Background: Proteasomes have six non-identical ATPases that move and unfold protein substrates. Results: Mutating homologous substrate contact residues of each ATPase has diverse effects on degradation and cell growth. Conclusion: Although homologous, each of the six has distinguishable functions. Significance: Structurally similar elements within a complex molecular machine can evolve distinct tasks, diversifying the range of accessible cellular responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 35 publications
7
58
0
Order By: Relevance
“…For example, ATP binding mutations in individual yeast Rpt subunits produced a range of effects that vary according to the subunit (22). As with other features of proteasome function (43), these findings suggest non-redundant roles for Rpt subunits in ATP-dependent proteasome assembly. In contrast, a recent report indicated that ATP binding mutations of any Rpt subunit blocked 26 S proteasome assembly in mammalian cells (44).…”
mentioning
confidence: 70%
“…For example, ATP binding mutations in individual yeast Rpt subunits produced a range of effects that vary according to the subunit (22). As with other features of proteasome function (43), these findings suggest non-redundant roles for Rpt subunits in ATP-dependent proteasome assembly. In contrast, a recent report indicated that ATP binding mutations of any Rpt subunit blocked 26 S proteasome assembly in mammalian cells (44).…”
mentioning
confidence: 70%
“…S12). The contrasting sidechain patterns of the pore loops-the hydrophobic pore-1 versus the highly charged pore-2 loops-suggest that they might play distinct roles in processive substrate translocation (36,45). We speculate that the pore-1 loops may propel substrates forward along the AAA channel through hydrophobic interactions, whereas the pore-2 loops translate their interactions with substrates into enhancement of ATP hydrolysis (46), possibly by controlling the configuration of the conserved glutamate residue in the Walker B motif (39) (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since the unfolding ability or processivity of both ClpXP and the proteasome are reduced by low complexity sequences such as the GRR from p105 or the GAr from EBNA1, and in both cases the primary mechanism is through a reduction in the ability of the protease to unfold and degrade the substrate rather than through accelerated release, it is likely that the basic mechanism underlying processivity has been conserved between bacteria and eukaroytes despite the evolutionary distance between them. Indeed, the proteasome Rpt motor ring shares a set of so-called "aromatic paddles" with bacterial unfoldases such as ClpX and HslU, and these paddles are predicted to be important for grabbing on to elements of the substrate and translocating them through the central pore (23,24). Aromatic paddle mutations have been associated with failures of processivity (although the kinetic basis is not known), so it seems likely that substrate modifications that reduce processivity will do so through an interaction with the aromatic paddles (23).…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments are necessary to determine how these paddles interact with the peptide chain and how these low complexity sequences affect said interaction. In the case of the proteasome, with six distinct ATPase subunits, it is also possible that some subunits are specialized for different sorts of pulling or holding interactions, or for pulling on different sorts of sequences (24,25).…”
Section: Discussionmentioning
confidence: 99%